2011
DOI: 10.1073/pnas.1116965108
|View full text |Cite
|
Sign up to set email alerts
|

Acrosome-reacted mouse spermatozoa recovered from the perivitelline space can fertilize other eggs

Abstract: Many investigators maintain that spermatozoa that have initiated the acrosome reaction (AR) before reaching the surface of the egg's zona pellucida (ZP) are unable to bind and penetrate the ZP. A recent study has revealed that most fertilizing mouse spermatozoa initiate the AR before contacting the ZP. We found that acrosome-reacted spermatozoa collected from the perivitelline space of Cd9-null mice (whose egg plasma membranes are incapable of fusing with spermatozoa) were able to pass through both the cumulus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(97 citation statements)
references
References 20 publications
5
89
1
2
Order By: Relevance
“…In the past, when spermatozoa acrosome reacted before binding to zona, it was called premature acrosome reaction and these spermatozoa were thought to have no fertilizing ability. However, the spermatozoa recovered from the perivitelline space could penetrate egg investments for the second time and fertilize eggs [30]. These results indicated that the timing of acrosome reaction is flexible, as indicated long ago in rabbit [54].…”
Section: Zona-induced Acrosome Reaction Must Be Reconsideredmentioning
confidence: 51%
See 1 more Smart Citation
“…In the past, when spermatozoa acrosome reacted before binding to zona, it was called premature acrosome reaction and these spermatozoa were thought to have no fertilizing ability. However, the spermatozoa recovered from the perivitelline space could penetrate egg investments for the second time and fertilize eggs [30]. These results indicated that the timing of acrosome reaction is flexible, as indicated long ago in rabbit [54].…”
Section: Zona-induced Acrosome Reaction Must Be Reconsideredmentioning
confidence: 51%
“…D) The modern view of the timing of acrosome reaction which take place independent to zona binding was strengthened by experiments demonstrating that acrosome reacted spermatozoa recovered from the perivitelline space could penetrate zona pellucida for the second time and fertilize eggs [30]. E) Only acrosome reacted spermatozoa can fuse with eggs.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, recently, the concept that the spermatozoa that have already undergone AR are unable to bind the ZP and have lost their fertilizing ability has been revamped. Indeed, Inoue and co-workers used AR spermatozoa collected from the perivitelline space of in vitro fertilized oocytes from Cd9-null mice to successfully fertilize eggs from WT mice, obtaining live offspring (Inoue et al, 2011). In addition, several molecules believed to play a key role in these SERB, once removed in KO mice, failed to exert their hypothesized role during fertilization (the KO mice were fertile).…”
Section: Introductionmentioning
confidence: 99%
“…Recent fi ndings have challenged this paradigm, and where, when, and what induces the AR are open questions again (Inoue et al 2011 ;Jin et al 2011 ;Kunzelmann et al 2011 ).…”
Section: Gaba and Glycine Receptorsmentioning
confidence: 99%
“…The fusion machinery involved in this reaction is regulated by Ca 2+ and similar to that found in many neuroendocrinal secretory cells (Bello et al 2012 ;Castillo Bennett et al 2010 ). Notably, where and what triggers the physiologically relevant AR is being reevaluated (Inoue et al 2011 ;Jin et al 2011 ;Visconti and Florman 2010 ;Yanagimachi 1998 ).…”
Section: The Acrosome Reactionmentioning
confidence: 99%